The Existence of Religious Studies in Sharia Regions: West Sumatra and Aceh - Sulthan Ahmad; Dwi Wahyuni; Muhammad Hidayat (Khazanah Pendidikan Islam, 2022)
So far, there have been many studies on the dynamics and development of the religious studies in Indonesia. In general, the study covers at least two major themes, namely historical development studies and methodological studies. Generally, the existing studies are dominantly based on the development and reflection of the Religious Studies in Yogyakarta, Jakarta and Bandung. However, it is not common to discuss religious studies in other areas such as West Sumatra and Aceh, which are sharia regions in Indonesia. This paper aims to find out how the existence of the Department of Religious Studies at UIN Imam Bonjol Padang and UIN Ar-Raniry Banda Aceh. Using a case study qualitative research method, this article shows that the Department of Religious Studies, both UIN Imam Bonjol Padang and UIN Ar-Raniry Banda Aceh, still exist in their respective regions. Although the two Department are still not well known by the public, the contribution of the two Department to religious life has provided a place to balance the religious life of the people of West Sumatra and Aceh. The real contributions that have been made to the Department of Religious Studies at UIN Imam Bonjol Padang and UIN Ar-Raniry Banda Aceh in West Sumatra and Aceh are, first, increasing religious inclusiveness; second, the driving force of religious moderation; third, activists of the discourse of tolerance; fourth, increasing inter-religious dialogue.